Antiglycation and antioxidant activities of oxyresveratrol extracted from the heartwood of artocarpus lakoocha roxb - Nasapon Povichit (2018)
From the heartwood of Artocarpus lakoocha, oxyresveratrol was isolated with a yield of 10%. The isolated oxyresveratrol showed strong antiglycation and antioxidant activities. The IC50 value for antiglycation was 2.0±0.03 μg/ml (five times higher than that of aminoguanidine), and the IC50 values for antioxidation were 0.1±0.01 mg/ml (DPPH method) and 0.43±0.03 mg/ml (TBARS method), which were nearly twice as strong as those of resveratrol. © 2010 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.